2016
DOI: 10.1007/s00246-016-1537-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Habitual Exercise and Performance on Cardiopulmonary Exercise Testing Differs Between Children With Single and Biventricular Circulations

Abstract: Background Increasing habitual exercise has been associated with improved cardiopulmonary exercise testing (CPET) performance, specifically maximal oxygen consumption in children with operatively corrected congenital heart disease. This has not been studied in children following Fontan palliation, a population in whom CPET performance is dramatically diminished. Methods A single-center cross-sectional study with prospective and retrospective data collection was performed that assessed habitual exercise prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…This has also been reported by other researchers who may have had too short duration of the intervention (95) hoping that the children would enjoy and continue exercising after the intervention. We did not find a correlation between maximal exercise capacity and quality of life, in line with the study by O'Byrne et al (97). Our results suggest that submaximal exercise capacity is more important for quality of life and, thus, well-being, rather than maximal exercise capacity.…”
Section: Physical Capacity Quality Of Life and Effects Of Exercise (Ii)supporting
confidence: 91%
“…This has also been reported by other researchers who may have had too short duration of the intervention (95) hoping that the children would enjoy and continue exercising after the intervention. We did not find a correlation between maximal exercise capacity and quality of life, in line with the study by O'Byrne et al (97). Our results suggest that submaximal exercise capacity is more important for quality of life and, thus, well-being, rather than maximal exercise capacity.…”
Section: Physical Capacity Quality Of Life and Effects Of Exercise (Ii)supporting
confidence: 91%
“…Reduced peak oxygen uptake in patients with CHD has previously been described by various studies. 3,[7][8][9][10][11] We could see that in patients with complex cardiac defects, peak oxygen uptake as percentage of reference values was significantly lower than in the group of non-complex defects. There were also differences between the groups separated by diagnosis, in which peak oxygen uptake showed a similar distribution as in the study by Kempny et al, with lowest values seen in patients with Fontan circulation.…”
Section: Cardiopulmonary Exercise Capacity In Chdmentioning
confidence: 72%
“…5,6 Multiple studies have shown a reduced cardiopulmonary exercise capacity amongst patients with CHD. 3,[7][8][9][10][11] This phenomenon can in part be traced back to consequences of the cardiac defect itself or its surgical or medical therapy, for example valve stenosis or insufficiencies, 3 stenosis of vessels as in coarctation of the aorta or Tetralogy of Fallot, 12 multiple thoracotomies, 13 or chronotropic incompetence under medical beta-blockade 14 or following Fontan procedure. 15 However, a lack of physical activity amongst these patients has also been identified as part of the reason for their reduced cardiopulmonary exercise capacity.…”
mentioning
confidence: 99%
“…Subjects underwent contemporaneous clinical assessment, review of medical history and testing as described previously 15 . The exercise questionnaire has been validated 16 and its application to children and adolescents has been described previously 15,17 . The second study included children and adolescents age 8–17.5 years with 1) transposition of the great arteries following an arterial switch operation (TGA) and 2) single ventricle heart disease who had undergone operative palliation culminating in a Fontan completion who were recruited prospectively between 3/1/2012–12/31/2013 at the time of a clinically indicated cardiopulmoanry exercise test 18 .…”
Section: Methodsmentioning
confidence: 99%